Hospital Wastewaters Characteristics, Management, Treatment and Environmental Risks (The Handbook of Environmental Chemistry,, 2018)
This volume addresses hospital effluents in terms of their composition and the management and treatment strategies currently (being) adopted around the globe. In this context, one major focus is on pharmaceutical compounds: their observed concentration range, ecotoxicological effects, and the removal efficiency achieved by the different technologies. Another focus is on management strategies (dedicated hospital wastewater treatment, or a combined approach also involving urban wastewater) and currently adopted treatments to reduce the released pollutant load. Innovative and promising technologies under investigation at the lab and pilot scale are presented. A discussion of remaining knowledge gaps and future research requirements rounds out the coverage. The respective chapters, written by experts in the different fields, provide useful information for a broad audience: scientists involved in the management and treatment of hospital effluents and wastewater containing micropollutants, administrators and decision-makers, legislators involved in the authorization and management of healthcare structure effluents, and environmental engineers involved in the design of wastewater treatment plants, as well as newcomers and students interested in these issues.